Battery management systems : accurate state-of-charge indication for battery powered applications - Pop, Valer. (Springer, 2017)
Battery Management Systems: Accurate State-of-Charge Indication for Battery-Powered Applications describes the field of State-of-Charge (SoC) indication for rechargeable batteries. With the emergence of battery-powered devices accurately estimating the battery SoC, and even more important the remaining time of use, becomes more and more important.An overview of the state-of-the-art of SoC indication methods including available market solutions from leading semiconductor companies, e.g. Texas Instruments, Microchip, Maxim, is given in the first part of this book. Furthermore, a universal SoC indication system that enables 1% or better accuracy under all realistic user conditions is developed. A possible integration with a newly developed ultra-fast recharging algorithm is also described.The contents of this book builds further on the contents of the first volume in the Philips Research Book Series, Battery Management Systems - Design by Modelling. Since the subject of battery SoC indication requires a number of disciplines, this book covers all important disciplines starting from (electro)chemistry to understand battery behaviour, via mathematics to enable modelling of the observed battery behaviour and measurement science to enable accurate measurement of battery variables and assessment of the overall accuracy, to electrical engineering to enable an efficient implementation of the developed SoC indication system. It will therefore serve as an important source of information for any person working in engineering and involved in battery management.